Architecture of client software for WEB-applications intended for data representation - Arushanian, O.B.; Bogomolov, N.A.; Kovalev, A.D.; Sinitsyn, M.N. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2004)
An approach to the development of WEB-applications intended for data representation is discussed. The approach is based on the extensive use of client software operating under standard Internet-browsers. Some advantages and disadvantages of this approach are considered. The architecture of client software, its object model, a hierarchy of classes, and a model of program events are given. The mechanism of dynamic downloading of programs and data from a server is described. The work was supported by the Russian Foundation for Basic Research (02-07-90236 and 04-07-90288).